CFD modelling of pollutant transport. Use of ANSYS Workbench® simulating emissions to air from vessel at Port of Breivika. - Madsen, Synne Karoline (UiT The Arctic University of Norway, 2019)
Historically, the Port of Tromsø is well known as the final port before entering the Arctic Sea. Nowadays, there is a noticeable traffic consisting of cruise vessels visiting Port of Tromsø before heading against the Arctic. The vessels transport passengers expecting clean air, midnight sun, northern lights, snow and ice; - and a clean environment. Environmental considerations and air pollution in all port areas should be expected to be given more focus in the future. The thesis presents Computational Fluid Dynamics (CFD) simulations in ANSYS® illustrating emissions of CO2 to air. CO2 is used as indicator because of its global climate impact. The literature review refers to CDF-simulations as a method to study pollution transport in urban environment. The two-phase model considers typical wind strength and wind direction in Tromsø. Data collection of coordinates and managing data was a time-consuming part of the thesis. The results from the simulations indicates a potential outcome if the weather conditions are optimal. The terrain in the model is recognizable for the port’s location. From the CFD results, it is illustrated that onshore wind with high wind strength could have effect on the environment near Port of Breivika. Mitigations to prevent pollution to air from vessels are presented. As a quality check, the model file was sent to ZHAW - Zürcher Hochschule für Angewandte Wissenschaften. The results simulated in OpenFOAM is qualitatively showing the same as visible in ANSYS®.